How transformational leadership shapes teacher job satisfaction: Evidence from public secondary schools in South-West Nigeria - Moses Adeleke Adeoye (UIN Raden Mas Said Surakarta, 2026)
Teacher job satisfaction remains a critical challenge in many public secondary schools in Nigeria, with important implications for teacher retention, instructional quality, and school effectiveness. Although transformational leadership has been widely recognized as an important leadership approach, empirical evidence regarding the relative contribution of its four dimensions to teacher job satisfaction in South-West Nigeria remains limited. This study investigated the relationship between principals' transformational leadership and teachers' job satisfaction across public secondary schools in Oyo, Ogun, and Ondo States. A quantitative correlational survey design was employed involving 72 principals and 731 teachers selected through proportional sampling. Data were collected using the Transformational Leadership Styles and Teachers' Job Satisfaction Questionnaire (TLSTJSQ), which demonstrated satisfactory reliability (Cronbach's α = 0.87). Descriptive statistics and multiple regression analysis were used for data analysis. The findings revealed that principals demonstrated a moderate-to-high level of transformational leadership (M = 3.08), while teachers reported moderate job satisfaction (M = 2.88), with intrinsic satisfaction exceeding extrinsic satisfaction. Transformational leadership was positively associated with teacher job satisfaction (R = 0.319, R² = 0.102, p < 0.05). Inspirational motivation emerged as the strongest predictor, followed by intellectual stimulation, individualized consideration, and idealized influence. These findings underscore the importance of strengthening transformational leadership competencies, particularly vision-building and intellectual engagement, to enhance teacher satisfaction and support school improvement initiatives.